The Relationship Between Self-Control and Tendencies Towards Narcissistic Behaviour in Teenagers Using Social Media TikTok - Nusantara, Wildhan Tri Darma; Syahputra, Yuda (Asosiasi Asesmen Pendidikan (AAP), 2025)
This study examines the relationship between self-control and narcissistic tendencies among adolescent TikTok users. This study aims to understand how the level of self-control impacts narcissistic behavior in adolescents who frequently use TikTok, given the popularity of this application and its potential influence on self-presentation and social validation seeking among adolescents. This study used a quantitative correlational approach, using a questionnaire to collect data from 150 respondents at SMA N 93 Jakarta. The analysis included descriptive statistics, normality tests, linearity tests, and Pearson correlations to test the relationship between self-control (independent variable) and narcissistic behavior (dependent variable) among TikTok users. This study found a significant relationship between self-control and narcissistic behavior among TikTok users, with a Pearson correlation coefficient of 0.393, indicating a weak correlation. Most respondents showed moderate levels of self-control and narcissistic tendencies. The results of the study indicate that increasing self-control can help reduce narcissistic behavior in adolescents. This study concludes that increasing self-control can reduce narcissistic behavior tendencies in adolescent TikTok users. Most respondents showed moderate levels of self-control, making it important to develop educational programs that focus on self-control skills to support the psychological development of adolescents in the digital era.